2017
DOI: 10.1111/ejss.12487
|View full text |Cite
|
Sign up to set email alerts
|

Plant exudates may stabilize or weaken soil depending on species, origin and time

Abstract: SummaryWe hypothesized that plant exudates could either gel or disperse soil depending on their chemical characteristics. Barley (Hordeum vulgare L. cv. Optic) and maize (Zea mays L. cv. Freya) root exudates were collected using an aerated hydroponic method and compared with chia (Salvia hispanica L.) seed exudate, a commonly used root exudate analogue. Sandy loam soil was passed through a 500‐μm mesh and treated with each exudate at a concentration of 4.6 mg exudate g−1 dry soil. Two sets of soil samples were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
178
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 173 publications
(189 citation statements)
references
References 45 publications
4
178
1
6
Order By: Relevance
“…Although exudation clearly represents a significant carbon cost to the plant, exudates are involved in engineering the rhizosphere by dispersion and gelling of soil (Naveed et al 2017;Barré and Hallett 2009;Tarchitzky and Chen 2002;Deng et al 2015), modulation of water and nutrient availabilities (Wang et al 2008;Ahmed et al 2014;Deng et al 2015), and attraction of rhizobacteria (Bais et al 2006). To our knowledge this is the first time that plant exudates have been demonstrated to ease soil compression and thus offer the potential for increased root elongation in soil.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although exudation clearly represents a significant carbon cost to the plant, exudates are involved in engineering the rhizosphere by dispersion and gelling of soil (Naveed et al 2017;Barré and Hallett 2009;Tarchitzky and Chen 2002;Deng et al 2015), modulation of water and nutrient availabilities (Wang et al 2008;Ahmed et al 2014;Deng et al 2015), and attraction of rhizobacteria (Bais et al 2006). To our knowledge this is the first time that plant exudates have been demonstrated to ease soil compression and thus offer the potential for increased root elongation in soil.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Naveed et al (2017) found that chia seed exudate has a greater amount of polysaccharide sugars and less organic acids than barley and maize root exudates, with differing impacts on soil rheology and water retention. Given the scale of samples required for compression experiments, however, harvesting real root exudates in sufficient quantities would be a formidable task.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is proposed that bioadhesive mucilage components of exudates are important factors, along with root hairs, in the formation of cylinders of soil around roots known as rhizosheaths. It appears that this will involve differing impacts on soil aggregation through varied viscosities and surface properties, on drying/wetting cycles and the potential for hydrophobicity of mucilage after drying and binding properties in general, including the sequestering of heavy metals (Ray et al, 1988;Watt et al, 1994;Dennis et al, 2010;Naveed et al, 2017;Kroener et al, 2018). Rhizosheath bioengineering by some grass species during periods of drought has been observed, where the grasses increased the thickness of their rhizosheaths (Hartnett et al, 2012).…”
Section: Root Exudates Bioengineer Rhizospheres For Sustained Resourcmentioning
confidence: 99%
“…Specifically, in the broad approach used to elucidate the entire root system, Walker et al (2003) found that the root exudates compounded with mucilage under certain circumstances exhibited a stabilizing effect on the rhizosphere (i.e., the stabilization of the soil structure near the roots). Naveed et al (2017) demonstrated that exudates from barley roots may disperse soil while exudates from maize roots and chia seed exudates may increase soil stability around roots or seeds. While the exudates lowered the surface tension of the soil pore water, similar to what the authors determined in this research (Figs.…”
Section: Exudate Effectsmentioning
confidence: 99%